An Analysis of Lexical Cohesion on the Students Thesis at the English Teaching Department of HKBP Nommensen University - Sihombing, Imnesti; Sidabutar, Usman; Tampubolon, Sahlan (LPPPI Publishing, 2024)
This study uses the type of lexical cohesion to analyze the writing of the background of study thesis. The purposes of this study are to find the type of lexical cohesion and what type of lexical is dominant in the background of the study thesis. This study was conducted using a qualitative method. The data collection method used document analysis because the data has taken from the text or document of the background of study thesis. The object of this research has the writing of the background of study thesis by students graduating in 2023. The results of this study are data on 10 background of thesis studies of students graduating in 2023. The researcher found 333 data on the use of lexical cohesion in the background of thesis of students graduating in 2023 consisting of 304 repetitions (91.6%), 3 synonyms (0.9%), 7 antonyms (2.1%), 9 hyponyms (2.7%), 10 meronyms (3.0%). From the results of the calculations above, the dominant type of lexical cohesion is repetition (91.6%).